2021
DOI: 10.31223/x5b61z
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale natural fracture network patterns: Insights from automated mapping in the Lilstock (Bristol Channel) limestone outcrops)

Abstract: Large-scale natural fracture network patterns: Insights from automated mapping in the Lilstock (Bristol Channel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Andresen et al (2013) and Vevatne et al (2014) report negative assortativity coefficients for fracture networks that are represented in the dual form. Prabhakaran et al (2021b) found such a correlation between dual graph node degree and length.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Andresen et al (2013) and Vevatne et al (2014) report negative assortativity coefficients for fracture networks that are represented in the dual form. Prabhakaran et al (2021b) found such a correlation between dual graph node degree and length.…”
Section: Introductionmentioning
confidence: 84%
“…To validate the proposed approach based on graph distance metrics and hierarchical clustering, we utilize a 2-D joint fracture dataset from the Lilstock pavement in the Bristol Channel, UK (Prabhakaran et al, 2021b). The dataset consists of fracture joints automatically traced using a technique described in from UAV photogrammetric data published by .…”
Section: Fracture Datasetsmentioning
confidence: 99%
“…We implement the fracture detection algorithm on 80 published outcrop maps [Duffy et al, 2017;Prabhakaran et al, 2021;Bertrand et al, 2015;Thiele et al, 2017;Odling, 1997;Jafari, 2011;Gillespie et al, 1993;Segall and Pollard, 1983b;Holland et al, 2009;Bisdom, 2016;Barton, 1995;Watkins et al, 2015;Healy et al, 2017;Becker et al, 2018;Odling et al, 1999;Wyller, 2019]. These outcrop maps are collected from different parts of the world as shown in Fig.…”
Section: Synthetic Analysis Of Fracture Geometries and Topological St...mentioning
confidence: 99%
“…We implement the fracture detection algorithm on 80 published outcrop maps [Duffy et al, 2017;Prabhakaran et al, 2021;Bertrand et al, 2015;Thiele et al, 2017;Odling, 1997;Jafari, 2011;Gillespie et al, 1993;Segall and Pollard, 1983b;Holland et al, 2009;Bisdom, 2016;Barton, 1995;Watkins et al, 2015;Healy et al, 2017;Becker et al, 2018;Odling et al, 1999;Wyller, 2019]. These outcrop maps are collected from different parts of the world as shown in Fig.…”
Section: Synthetic Analysis Of Fracture Geometries and Topological Structuresmentioning
confidence: 99%